Pengaruh Waktu Pencampuran terhadap Kekerasan Vickers Material Crucible Berbahan Limbah Evaporation Boats, Kaolin dan Semen Tahan Api - Triyanto, Sandy; Rusiyanto, Rusiyanto; Widodo, Rahmat Doni; Anis, Samsudin; Fitriyana, Deni Fajar (Jurnal Rekayasa Mesin, 2021)
Evaporation boat waste contains Boron Nitride (BN) and Titanium Diboride (TiB2) so that it has electrically conductive properties with high resistance to chemicals and heat. In addition, the combination of these materials has high thermal conductivity properties with a melting point of up to 2700oC and has an oxidation resistance of up to 1000oC so it is very suitable if applied to crucibles, or refractory. The purpose of this study was to determine the effect of mixing duration on the hardness of the crucible material made from a mixture of evaporation boats waste, kaolin and fire mortar SK-34. The mixing process of evaporation boats waste, kaolin and refractory cement is carried out using a mixer machine with a duration of 30, 60 and 90 minutes. The compaction process was carried out on the mixture with a force of 40 kg/cm2 to produce a cylindrical test specimen. After seven days, the specimens were sintered at 1000oC for 2 hours. The hardness test process was carried out with the FM-800 microhardness tester machine to determine the effect of mixing duration on the final product hardness. The highest hardness of 37,2 HV was found in the final product with a mixing duration of 90 minutes. The hardness of final product is increasing with an increase in mixing duration.